Single-Cell RNA-seq Identifies Cell Subsets in Human Placenta That Highly Expresses Factors Driving Pathogenesis of SARS-CoV-2 - Ashary, Nancy; Bhide, Anshul; Chakraborty, Priyanka; Colaco, Stacy; Mishra, Anuradha; Chhabria, Karisma; Jolly, Mohit Kumar; Modi, Deepak (Frontiers in Cell and Developmental Biology, 2020)
Infection by the Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) results in the novel coronavirus disease COVID-19,. Infection of SARS-CoV-2 during pregnancy is associated with complications such as preterm labor and premature rupture of membranes, and a proportion of neonates born to infected mothers are also positive for the virus. During pregnancy, the placental barrier protects the fetus from pathogens. To predict if the placenta is permissive to SARS-CoV-2, we utilized publicly available single-cell RNA-seq data to identify if the placental cells express the factors required for infection. SARS-CoV-2 binding receptor ACE2 and the S protein priming protease TMPRSS2 are co-expressed by a subset of syncytiotrophoblasts (STB) in the first trimester and extravillous trophoblasts (EVT) in the second trimester . In addition, the non-canonical receptor BSG/CD147 and other proteases (CTSL, CTSB and FURIN) are detected in most of the placental cells. Other coronavirus family receptors (ANPEP and DPP4) were also expressed in the first and second trimester placental cells. Additionally, the term placenta of multiple species including humans expressed ACE2, DPP4 and ANPEP along with the viral S protein proteases. The ACE2- and TMPRSS2-positive (ACE2+TMPRSS2+) placental subsets expressed mRNA for proteins involved in viral budding and replication. These cells also had the mRNA for proteins that physically interact with SARS-CoV-2 in host cells. Further, we discovered unique signatures of genes in ACE2+TMPRSS2+ STBs and EVTs. The ACE2+TMPRSS2+ STBs are highly differentiated cells and express genes involving mitochondrial metabolism and glucose transport. The second trimester ACE2+TMPRSS2+ EVTs are enriched for markers of endovascular trophoblasts. Both these subtypes abundantly expressed genes in the Toll-like receptor pathway. The second trimester EVTs are also enriched for components of the JAK-STAT pathway that drives inflammation. We carried out a systematic review and identified that in 12% of pregnant women with COVID-19, the placenta was infected with SARS-CoV-2, and the virus was detected in STBs. To conclude, herein we have uncovered the cellular targets for SARS-CoV-2 entry and have shown that these cells can potentially drive viremia in the developing human placenta. Our results provide a basic framework towards understanding the paraphernalia involved in SARS-CoV-2 infections in pregnancy.